Carbon and hydrogen stable isotope fractionation due to monooxygenation of short-chain alkanes by butane monooxygenase of Thauera butanivorans Bu-B1211 - Vogt, Carsten; Song, Zhiyong; Richnow, Hans-Hermann; Musat, Florin (Frontiers in Microbiology, 2023)
Multi element compound-specific stable isotope analysis (ME-CSIA) is a tool to assess (bio)chemical reactions of molecules in the environment based on their isotopic fingerprints. To that effect, ME-CSIA concepts are initially developed with laboratory model experiments to determine the isotope fractionation factors specific for distinct (bio)chemical reactions. Here, we determined for the first time the carbon and hydrogen isotope fractionation factors for the monooxygenation of the shortchain alkanes ethane, propane, and butane. As model organism we used Thauera butanivorans strain Bu-B1211which employs a non-haem iron monooxygenase (butane monooxygenase) to activate alkanes . Monooxygenation of alkanes was associated with strong carbon and hydrogen isotope effects: εbulkC = -2.95 ± 0.5 ‰ for ethane, -2.68 ± 0.1 ‰ for propane, -1.19 ± 0.18 ‰ for butane; εbulkH = -56.3 ± 15 ‰ for ethane, -40.5 ± 2.3 ‰ for propane, -14.6 ± 3.6 ‰ for butane. This resulted in lambda (Λ ≈ εHbulk/εCbulk) values of 16.2 ± 3.7 for ethane, 13.2 ± 0.7 for propane, and 11.4 ± 2.8 for butane. The results show that ME-CSIA can be used to track the occurrence and impact of monooxygenase-dependent aerobic processes converting short-chain alkanes in natural settings like marine and terrestrial seeps, gas reservoirs, and other geological formations impacted by natural gas.